EDUCATIONAL LEARNING RESOURCE NEED OF 21ST CENTURY UNIVERSITY LIBRARY BUILDINGS IN NIGERIA - Akande, Oluwafemi; Obi-George, Lilian; Anyawu , Collins; Anikor, Emmanuel; Makun, Charles; Basil, Amaka-Anolue (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2024)
The library as a core educational learning center should reflect the current revolution in the use of information and communication technologies (ICTs) for academic learning. However, due to current advancements in the use of ICTs, old library buildings are gradually becoming obsolete. Users' visits to libraries will continue to drop until the obsolescence of the library buildings is addressed and creative learning spaces are established. Many university library buildings in Nigeria have not been modernised to satisfy the educational learning needs of the users they serve in the twenty-first century. This study examines users' perceptions of university library buildings in Nigeria. The objective is to determine users' educational learning resource demands and library building expectations that suit their 21st century needs as learners. A quantitative research methodology was used, with questionnaires (n= 484) distributed to users of libraries at selected educational institutions of higher learning in Nigeria. Findings shows that users were pleased with the indoor ambient conditions of the libraries, but were dissatisfied with the insufficient facilities and provision that met their 21st century learning demands. The paper suggests that educational institutions should constantly examine the learners' requirements in order to match their current educational needs. This would allow them to provide and/or upgrade their library buildings, which would improve users' learning while also meeting the needs of 21st century library users. It concluded that outmoded library buildings are a reflection of poor educational outcomes, which are invariably responsible for making library buildings irrelevant to users.